Supporting the mental health of mothers of children with a disability: Health professional perceptions of need, role, and challenges. (9th August 2018) - Gilson, Kim‐Michelle; Johnson, Shae; Davis, Elise; Brunton, Susan; Swift, Elena; Reddihough, Dinah; Williams, Katrina
Abstract: Background: Mothers of children with a disability have a higher risk of mental health difficulties than mothers of typically developing children. Very little is known about how health professionals perceive their role in supporting mothers' mental health. We aimed to explore the perspectives of health professionals working with families of children with a disability about how they provide support for maternal mental health in their roles. Specifically, whether professionals consider it their role and responsibility to provide support, the types of actions that they engage in to do this, and the challenges that they experience. Methods: This qualitative semi‐structured interview study included 13 health professionals (allied health professionals, general practitioners, and paediatricians) working with families of a child with a disability. Thematic analysis was conducted on transcribed interview data. Results: Four overlapping themes were identified from the data indicating that professionals knew that mothers needed mental health support but were not always clear about their roles and responsibilities to support maternal mental health. Professionals also found it difficult to address maternal mental health difficulties, were not always aware of the best strategies to support maternal mental health, and faced difficulties that could be overcome with training and system improvements. Conclusions: Although all health professionals were aware of the frequent occurrence of maternal mental health difficulties and the importance of addressing them, several challenges were identified to managing them successfully. Providing health professionals with training in discussing mental health and clearer referral pathways would contribute to mothers being better supported, in addition to policy change that allows parental support in child health services.